The use of the new Tropical Forages Selection Tool by research, academia, farmers and other actors in the global Tropics - CGIAR Research Program on Livestock (2021)
The Tropical Forages Selection Tool (TF) is an open-access online knowledge system used by researchers, educators, extensionists and livestock/forage producers from Latin America, Asia and Africa to obtain expert information on 172 major forages in tropical/sub-tropical areas. Since the release of a new online, mobile version in 2020 that incorporates 15 years of forage research advances, unique user numbers doubled to 80,000. The tool is considered a foremost guide in the selection of forages to suit specific environments.